Designing Decentralized Digital Product Passports: A Path to Circular Economy Implementation - Ashutosh Dhar Dwivedi; Reza Tadayoni (International Telecommunications Society (ITS), 2025)
The global transition towards a circular economy demands the creation of advanced digital tools that enable transparency, trust, and sustainability across product lifecycles. Decentralized Digital Product Passports (DPP) are emerging as a transformative solution to address these challenges. This paper investigates digital product passports based on distributed ledger and Internet of Things (IoT) technologies. The framework aims to securely record, store, and share product-related data, such as material composition, environmental impact, and usage history, in a tamper-proof and decentralized manner. Using the immutable nature of distributed ledgers and integrating real-time IoT data collection, the DPP framework aligns stakeholder actions with circular economy objectives, including improved resource efficiency, increased product reuse, and optimized recycling processes.
Keywords: 330